Psychosocial Factors and the Role of Family in Children with Type 1 Diabetes Mellitus - Dhanya Soodhana Mohan; Vani HN; Rajendra Kiragsur Madegowda; Raghupathy Palany (Dubai Diabetes and Endocrinology Journal)
Purpose: The psychosocial aspects of type 1 diabetes mellitus (T1DM) are still a neglected area, especially among children in India. This study was planned to evaluate and screen the children with T1DM for family support, symptoms of anxiety and depression, and to assess the role of these psychosocial aspects in glycemic control. Methods: This cross-sectional observational questionnaire-based study conducted over a year included 70 children aged 8–18 years diagnosed with T1DM for at least a year. The child and caregiver answered pre-validated standard questionnaires and the children underwent HbA1C testing once every 3 months. The methods used for inferential statistical analysis were reliability analysis, correlation analysis, χ2 test, and factor analysis. Results: Poorer glycemic control was noted by children raised by single parents (mean HbA1C 14.4, p < 0.001). It was also noted that children whose mothers had formal education beyond 10th standard had better glycemic control. 14 children (20%) had anxiety/depression of medium to high severity. The relationship between family conflict and glycemic control was not significant in either the parent or the child scoring. Conclusion: Children with T1DM experience considerable stress related to the diagnosis and management. Many families experience significant depression and anxiety which leads to increase in family conflicts which have a negative effect on parenting, the child’s quality of life, and their glycemic control.